Feedback Linearization With Intelligent Disturbance Observer For Autonomous Quadrotor With Time-varying Disturbance - Izzuddin M. Lazim; Abdul Rashid Husain; Mohd Ariffanan Mohd Basri; Nurul Adilla Mohd Subha (IJENS Publisher, 2024)
International Journal of Mechanical & Mechatronics Engineering IJMME-IJENS Vol:18 No:05